An interdigitated electrode with dense carbon nanotube forests on conductive supports for electrochemical biosensors. Issue 15 (29th June 2018) - Sugime, Hisashi; Ushiyama, Takuya; Nishimura, Keita; Ohno, Yutaka; Noda, Suguru
Abstract : A highly sensitive interdigitated electrode (IDE) with vertically aligned dense carbon nanotube forests directly grown on conductive supports was demonstrated by combining UV lithography and a low temperature chemical vapor deposition process (470 °C). Abstract : A highly sensitive interdigitated electrode (IDE) with vertically aligned dense carbon nanotube forests directly grown on conductive supports was demonstrated by combining UV lithography and a low temperature chemical vapor deposition process (470 °C). The cyclic voltammetry (CV) measurements of K4 [Fe(CN)6 ] showed that the redox current of the IDE with CNT forests (CNTF-IDE) reached the steady state much more quickly compared to that of conventional gold IDE (Au-IDE). The performance of the CNTF-IDE largely depended on the geometry of the electrodes ( e.g. width and gap). With the optimum three-dimensional electrode structure, the anodic current was amplified by a factor of ∼18 and ∼67 in the CV and the chronoamperometry measurements, respectively. The collection efficiency, defined as the ratio of the cathodic current to the anodic current at steady state, was improved up to 97.3%. The selective detection of dopamine (DA) under the coexistence ofl -ascorbic acid with high concentration (100 μM) was achieved with a linear range of 100 nM–100 μM, a sensitivity of 14.3 mA mol −1 L, and a limit of detection (LOD, S/N = 3) of 42 nM. Compared to the conventional carbon electrodes, the CNTF-IDE showed superior anti-fouling property, which is of significant importance for practical applications, with a negligible shift of the half-wave potential (Δ E 1/2 < 1.4 mV) for repeated CV measurements of DA at high concentration (100 μM).